18 CLINICAL PRACTITIONERS' EDUCATION AND RESOURCE NEEDS FOR INFLAMMATORY BOWEL DISEASES. (7th February 2019) - Malter, Lisa B; Jain, Animesh; Cohen, Benjamin; Gaidos, Jill; Axisa, Lisa; Butterfield, Lori; Rescola, Becky Johnson; Sarode, Sudha; Cheifetz, Adam; Ehrlich, Orna G
Abstract: Background: As treatments, management strategies, and the role of advanced practice providers has evolved in recent years, the Crohn's & Colitis Foundation sought to understand the educational and resource needs of clinicians caring for patients with inflammatory bowel diseases (IBD). The aim of this study is to describe the self-identified IBD knowledge and resource gaps of clinicians. Methods: A survey containing 19 questions created by the Foundation's Professional Education Committee, a subset of their National Scientific Advisory Committee, was conducted from 9/7/18-10/15/18. Respondents were eligible if they currently see any IBD patients in a clinical setting. The Foundation communicated the survey by email and various social media channels to encourage a diverse response. The survey asked questions on comfort level around diagnosis, treatment, and management of patients with IBD as well as preferences and utilization of resources. Analysis was conducted by Yasamin Miller Group and all responses were included. Results: There were 200 eligible responses, of which the majority were MD/DO (75.61%) followed by APN/PA (13.01%) and 70% of the respondents provide care for adult patients. The amount of time in practice was divided evenly amongst respondents. Over 50% of respondents reported practicing in an academic/university setting and 75% stated that 35% or more of their practice was made up of patients with IBD. A minority of respondents have access to IBD based mental health providers or social workers in their practice although most have access to surgeons, radiologists, pathologists and dieticians. The areas of greatest educational need were: prescribing medical cannabis (if approved in state) for pain management (62%), caring for patients with prior malignancy (35%), caring for pregnant patients and family planning (34%), caring for elderly patients (30%) (Figure 1) and therapy decisions, including use of JAK inhibitors (28%), drug holidays (25%) and biosimilars (24%) (Figure 2). Over 50% of respondents stated they do not participate in shared decision-making citing time as the most common limiting factor. The majority of providers cited live learning as their preferred learning format and wish to earn CME hours. Conclusion: This survey helps identify the current IBD needs in our professional community. With a rapidly changing treatment landscape and an increase in the diversity of providers delivering care, additional opportunities to keep abreast of practice changes are critical to providing comprehensive, quality care in IBD. Improved access to resources to efficiently utilize shared decision-making in practice was demonstrated. Based on our results a focus on creating live learning opportunities that offer CME are needed in the areas of therapeutic decision-making and treating IBD in special subsets (prior malignancy, pregnancy, elderly).